ANALYSIS OF FACTORS RELATED TO THE EVENT OF PRIMARY DYMENOROREA IN ADOLESCENT WOMEN IN SITINJAU LAUT DISTRICT - Puspita Sari; Lia Nurdini; Fefi Tri Yuzela; Fitria Eka Putri; Solihin Sayuti (Pusat Riset dan Inovasi Nasional, 2022)
Primary dysmenorrhea is menstrual pain that is found without obvious abnormalities of the genital organs. Primary dysmenorrhea often occurs in adolescent girls aged 10-14 years (early adolescence). Primary dysmenorrhea refers to pain without obvious pathological pelvic disease or menstrual pain with normal pelvic anatomy, usually beginning in adolescence after their ovulatory cycle has established. The purpose of this study was to determine the relationship between age of menarche, duration of menstruation and exercise habits in adolescent girls in Sitinjau Laut District. This research is a quantitative research with a cross sectional design. Data collection was carried out in March-April 2021. The research population was... Young Women with a research sample of 198 young women. Sampling was done by using proportional random sampling technique. This study consisted of the independent variable